ОТРАЖЕНИЕ ГЛУБИННОГО СТРОЕНИЯ ЗАБАЙКАЛЬЯ В ПЛАНОВОЙ КОНФИГУРАЦИИ ДОЛИННОЙ СЕТИ И В ДЕФОРМАЦИЯХ ПРОДОЛЬНЫХ ПРОФИЛЕЙ РЕК - Крячкова Р.В. (My University, 2004)
Geodynamics of lithosphere structures of different depth, and anomalies of geophysical fields affect the plan pattern of the drainage network, the longitudinal profiles, and valleys morphology.
Keywords: 551.432—)551.435.11(—925.16)